Pengaruh Kualitas Layanan Terhadap Kepuasan Pemustaka Di Upt Perpustakaan Universitas Halu Oleo - Kalsum, Umi; Tarifu, La; Ibrahim, Cecep (Ilmu Informasi Perpustakaan dan Kearsipan, 2023)
This study aims to determine the effect of service quality on user satisfaction at the Halu Oleo University Library UPT (HaluOleo University Student Thesis Study). This study used a quantitative approach by distributing questionnaires to UHO students. The tests carried out in this study were validity, reliability, linear regression and correlation tests. The sample in this study was 193 respondents taken from the population using random sampling technique. The results of this study indicate that there is a significant influence between service quality and user satisfaction. The R square results found that the effect of service quality on user satisfaction can be explained by 23.6%. This proves that the effect of service quality on user satisfaction is in accordance with the interpretation of the correlation coefficient, namely 0.20 - 0.399 which is in the low category. While the remaining 76.4% is explained by other variables not included in this study.